Architecture of the endoplasmic reticulum plays a role in proteostasis. Issue 4 (3rd April 2022) - Parashar, Smriti; Ferro-Novick, Susan
ABSTRACT: The endoplasmic reticulum (ER) forms a contiguous network of tubules and sheets. When errors in protein folding occur, misfolded proteins accumulate in the ER. Proteostasis can be restored by ER quality control pathways. Reticulophagy is an ER quality control pathway that uses resident autophagy receptors to link an ER domain to the autophagy machinery. We recently showed that the reticulophagy receptor RTN3L recruits the COPII cargo adaptor SEC24C to target disease-causing mutant proinsulin INS2 Akita puncta to the lysosome for degradation. When reticulophagy is disrupted and delivery to the lysosome is blocked, large INS2 Akita puncta accumulate in the ER. Photobleach analysis revealed that these puncta behave like liquid condensates and not aggregates, as previously suggested. Other reticulophagy substrates that are segregated into tubules behave like INS2 Akita, whereas a substrate of the ER sheets receptor, RETREG1/FAM134B, appears to be less fluid. Large INS2 Akita puncta also accumulate when ER sheets are proliferated by the loss of LNPK, or by overproduction of the sheets-producing protein, CKAP4/CLIMP63. Restoring the tubular network by overexpressing reticulons reverses this phenotype. Our findings revealed that fluid-like deleterious cargoes are segregated into tubules to prevent them from expanding and affecting cell health while they are waiting to undergo reticulophagy.